2020
DOI: 10.1126/sciadv.aax6646
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound delivery of a selective TrkA agonist rescues cholinergic function in a mouse model of Alzheimer’s disease

Abstract: The degeneration of cholinergic neurons is a prominent feature of Alzheimer’s disease (AD). In animal models of injury and aging, nerve growth factor (NGF) enhances cholinergic cell survival and function, contributing to improved memory. In the presence of AD pathology, however, NGF-related therapeutics have yet to fulfill their regenerative potential. We propose that stimulating the TrkA receptor, without p75NTR activation, is key for therapeutic efficacy. Supporting this hypothesis, the selective TrkA agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 55 publications
2
46
0
Order By: Relevance
“…We have also previously shown that the application of SUS achieves BBB opening throughout the brain [17] and, consequently, results in higher brain concentrations of antibodies in an IgG format, with up to 2% of the injected dose reaching the brain as compared to 0.2% without SUS [23]. Studies by us in Tau transgenic mice [22, 23] and work by others [24, 35] have suggested that ultrasound can also be used as an effective drug delivery tool to increase levels on antibodies in the AD brain.…”
Section: Discussionmentioning
confidence: 95%
“…We have also previously shown that the application of SUS achieves BBB opening throughout the brain [17] and, consequently, results in higher brain concentrations of antibodies in an IgG format, with up to 2% of the injected dose reaching the brain as compared to 0.2% without SUS [23]. Studies by us in Tau transgenic mice [22, 23] and work by others [24, 35] have suggested that ultrasound can also be used as an effective drug delivery tool to increase levels on antibodies in the AD brain.…”
Section: Discussionmentioning
confidence: 95%
“…We have also previously shown that the application of SUS achieves BBB opening throughout the brain [ 17 ] and, consequently, results in higher brain concentrations of antibodies in an IgG format, with a 19-fold higher concentration of IgG reaching the brain as compared to peripheral injection without SUS [ 23 ]. Studies by us in tau transgenic mice [ 22 , 23 ] and work by others [ 24 , 36 ] have suggested that ultrasound can also be used as an effective drug delivery tool to increase the level of antibodies in the AD brain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of a 2018 clinical trial showed that intranasal administration of NGF could improve cognitive function in two patients with frontotemporal dementia 53 , suggesting a role for NGF in adult human CNS function. The results of these studies [49][50][51][52][53] imply that an intact blood-brain barrier is a prerequisite for the treatment of elderly individuals with NGF inhibitors. Therefore, any patient population with an impaired blood-brain barrier, such as after stroke and in those with multiple sclerosis, Alzheimer disease or neuroinflammatory disorders 54 , should be excluded from treatment with NGF inhibitors.…”
Section: Fig 1 | the Evolution Of Ngf Inhibition In Clinical Medicinementioning
confidence: 99%
“…This effect is transient, reversible and dependent on the stage of postnatal development. NGF might also have a role in Alzheimer disease, as there seems to be a degeneration of cholinergic neurons in the basal forebrain and hippocampus in mice with an experimental model of this disease 52 . Furthermore, the results of a 2018 clinical trial showed that intranasal administration of NGF could improve cognitive function in two patients with frontotemporal dementia 53 , suggesting a role for NGF in adult human CNS function.…”
Section: Fig 1 | the Evolution Of Ngf Inhibition In Clinical Medicinementioning
confidence: 99%